Augmented Reality and Virtual Reality Empowering Human, Place and Business (Progress in IS,, 2018)
This volume provides the latest outcomes of augmented reality (AR) and virtual reality (VR) research conducted in various industries. It reveals how AR and VR are currently changing the business landscape, and how new innovations provide opportunities for businesses to offer their customers unique services and experiences. Collecting the proceedings of the International AR & VR Conference held in Manchester, UK, in February 2017, the book advances the state of the art in AR and VR technologies and their applications in various industries such as tourism, hospitality, events, fashion, entertainment, retail, education and the gaming industry. The papers presented here cover the most significant topics within the field of AR and VR for both researchers and practitioners, approaching them from a business and management perspective. .